Incorporating construction and demolition waste into non-load brearing bricks. - Soliman, Neveen samy Talaat (AUC Knowledge Fountain, 2014)
Egypt faces serious solid waste management challenges. Currently, waste is either burned or dumped along roads and canals. Not only do these wastes cause health problems, but they also contribute significantly to soil, air, and water pollution. Solid waste can be categorized as residential, industrial, institutional, municipal, manufacturing, and construction and demolition waste (C&DW). The construction industry threatens the environment in three main ways: during the production of raw materials in the process of cement and aggregate production; during the construction process itself due to high consumption of energy; and, in the final stages of the construction process due to demolition waste disposal problems. It is a common practice at the end of the lifecycle of a building in Egypt to demolish it, leaving the construction and demolishing waste without proper waste management. This underscores the unfortunate fact that the concept and practices of adequate recycling are still not applied in Egypt. This study aims at exploring potential uses for construction waste in feasible applications. More specifically, it targets the possibility of employing construction and demolition waste to produce non-load bearing bricks that is suitable for use in the construction industry. A case study is provided to highlight the socio-economic value of recycling. In addition, a cost and benefit analysis is included in which the feasibility of the proposed bricks is explored. To meet this objective, standard tests, such as compressive strength, flexural strength, water absorption and density, were performed on the bricks. The results of this study reveal that the final product meets expected properties of standard bricks used in construction. The case study demonstrates that the impact of using bricks made from construction and demolition waste extends beyond the technical and functional to include socio-economic and environmental positive impacts. The cost and benefit analysis pinpoints that applying the recycling concept in this area also offers financial merits; this provides an incentive for the use of such products in future construction projects. Recommendations for future work to further validate the findings of this study are presented.